Adverse impact of a high CD4/CD8 ratio in the allograft may be overcome by methotrexate‐ but not mycophenolate‐ or post‐transplant cyclophosphamide‐based graft versus host disease prophylaxis. (28th March 2023) - Nikoloudis, A.; Buxhofer‐Ausch, V.; Aichinger, C.; Binder, M.; Hasengruber, P.; Kaynak, E.; Wipplinger, D.; Milanov, R.; Strassl, I.; Stiefel, O.; Machherndl‐Spandl, S.; Petzer, A.; et al.
Abstract: Introduction: A high CD4/CD8 T cell ratio in hematopoietic stem cell transplant (HSCT) allografts was observed to predict graft‐versus‐host disease (GVHD) and nonrelapse mortality (NRM) but has not been comparatively examined in settings of various GVHD‐prophylaxis regimens. Methods: This retrospective monocentric study included all consecutive HSCT performed with peripheral blood stem cells between January 2000 and June 2021. The impact of the graft CD4/CD8 ratio was analyzed in three cohorts with different GVHD‐prophylaxis platforms. Results: In the cyclosporine/mycophenolate‐mofetil (CSA/MMF) cohort ( n = 294, HLA‐matched HSCT), a high (>75th percentile) CD4/CD8 ratio was associated with increased overall mortality (HR: 1.56; p = .01), increased NRM (HR: 1.85; p = .01) and GVHD‐associated mortality (HR: 2.13; p = .005). In the post‐transplant cyclophosphamide (PTCy)/tacrolimus/MMF cohort ( n = 113, haploidentical‐related or mismatched‐unrelated HSCT), a high CD4/CD8 ratio was associated with increased overall mortality (HR 2.07; p = .04) and aGVHD3‐4 (HR: 2.24; p = .02). By contrast, in the CSA/methotrexate (CSA/MTX) cohort ( n = 185, HLA‐matched HSCT) the CD4/CD8 ratio had no significant impact on any of the investigated endpoints. Conclusion: A high CD4/CD8 ratio in the allograft has an adverse impact on GVHD and survival in CSA/MMF‐ and PTCy‐based HSCT, while MTX‐based prophylaxis may largely alleviate this important risk factor.